Acute abdomen due to axial torsion of Meckel's diverticulum - Gulan Maree; Alaa Ghuzlan; Hanna Kassab; Ali Alelayan; Ibrahem Sheikh Mohamad; Wajih Ali (Elsevier, 2022)
Meckel's diverticulum is a remnant of the omphalomesenteric duct and is the most common congenital anomalies of the gastrointestinal tract. The complications of MD include hemorrhage, perforation, intestinal obstruction, and inflammation. Torsion is one of the rarest complications of MD, and only a few reports exist that discuss this complication. We report a case of a 2.5-year-old male who presented with signs of acute abdomen. Dilated small bowel loops, gangrenous and axially torsional Meckel's diverticulum were found intraoperatively. Diverticulectomy was performed without ileal resection. The patient was discharged in good condition with no complications occurring during follow-up for 2 months. In the English literature, About 6 cases in children and less than 20 cases in adults of MD with axial torsion have been reported.